Diachronic complexification and isolation - Baechler, Rafaella (Yearbook of the Poznan Linguistic Meeting, 2014)
One may hear that over time languages tend to simplify their grammar and notably their morphological system. This intuition, probably based on linguists’ knowledge of the rich inflectional systems of older Indo-European languages, has been challenged, particularly by sociolinguistic typologists (e.g. Trudgill 2011; Braunmuller 1984, 2003; Nichols 1992). They hypothesise that languages spoken by small and isolated communities with a dense network may complexify their grammar (Trudgill 2011: 146-147). The present article investigates the nominal inflection systems of 14 varieties of German in order to survey whether there is any such diachronic tendency towards simplification and whether instances of complexification can be observed, too. The varieties under analysis include present-day Standard German, Old High German and Middle High German (two older stages of German) and eleven present-day non-standard varieties which make part of the Alemannic dialect group. First, it will be shown that there is a diachronic tendency towards simplification if we consider the total complexity of nominal inflection. Second, however, we can identify instances of diachronic complexification too if we take a closer look at single categories. Interestingly, diachronic complexification appears only in the non-standard varieties, not so in the standard variety. This may support the hypothesis that isolated varieties are more complex than non-isolated ones.